Analisis Wacana Kritis atas Opini Publik terhadap Kinerja Pemerintah dalam Survei Kawula17 2025 - Nova Azzahra Ramadhani; Mochamad Arif Affandi; Fransiscus Xaverius Sri Sadewo (MAN 4 Kota Pekanbaru, 2026)
Public opinion surveys are widely used as indicators of governmental legitimacy. However, quantitative approaches often fail to capture the complex meanings embedded in public responses. This study highlights the importance of discourse analysis in interpreting survey data, particularly amid declining public trust in the Indonesian government during Q2 2025. This research applies Norman Fairclough’s Critical Discourse Analysis (CDA) to secondary data from the Kawula17 Q2 2025 Survey. The analysis follows three dimensions: textual, discursive practice, and social practice, focusing on issues of corruption, economy, and gender legislation (RUU PPRT). Public opinion emerges as a discursive construction marked by ambivalence, symbolic resistance, and critique of power relations. Expressions like “death penalty for corruptors” and “the little people are suffering” reflect tensions between state narratives and citizens’ lived realities. Public opinion is not neutral; it is shaped by social structures and dominant ideologies. CDA offers a critical lens to reinterpret political surveys as socially embedded texts.